The journey through imagination: Francesca. Issue 2 (1st October 2018) - Ippolito, Valentina
Over the past decade, Romanian New Wave (Noul Val) has emerged as a vital component of European cinematic identity, with a number of its films representing stories of diasporic migration within an historical context set before and after Romania's accession to the European Union. This migration cinema has been a flourishing artistic tool for social criticism, bringing on-screen stories of crime, social degradation and corruption connected to journeys away from Romania, a number of which have Italy as their target. Recent scholarship has identified sociopolitical themes associated with Romanian migration cinema and the cinematic representation of marginalized identities. However, critical attention has so far overlooked the analysis of the recurrent presence of Italy in Romanian films, especially as an index of the extent to which the voice of the Romanian migrant is allowed to penetrate contemporary cinematic narratives. To address this critical gap, this article examines the expressive modes used by Noul Val director Bobby Paunescu to represent Italy in his film Francesca. Experienced by characters as a dead end for utopian desire, this article illustrates how the journey to Italy culminates in failure, disenchantment and grief.